The Sufi Function In Artistic Features: A Reference Reading In Modern European Plastic Arts - Mohamed Badir; Ahmed Benazza (The Journal of Studies in Language, Culture and Society, 2025)
Literary and artistic works have conveyed multiple discourses, particularly the Sufi indications, as a means of searching for absolute truth. This perspective is often embraced by a group that has led a life of asceticism, piety, and seclusion, to immerse the self in servitude and shed the reprehensible traits of human nature. The goal is to subject oneself to divine commands, find peace, and submit to the judgments of divine sovereignty. These influences have extended to global art schools, serving as material and psychological scientific discoveries of a lost dream that the self-strives to reach, particularly in plastic paintings. Various sciences, including anthropology and philosophy, have allowed us to deconstruct the relationship of art and Sufism. This has established harmony and coherence of the artist and the mystic, enabling them to journey with their individuality towards absolute happiness and achieving cultural partnership among humans.